Pendekatan Storytelling Marketing Dalam Meningkatkan Brand Produk Lokal - Heni Indriani; Dhanurseto Hadiprashada (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2026)
This study aims to analyze the implementation of a storytelling marketing approach in enhancing the Brand of local product samong Micro, Small, and Medium Enterprises (MSMEs) in North Bengkulu. This study employs a qualitative approach with a constructivist paradigm to understand the process of meaning-making in narrative-based marketing communication practices. Data were collected through in-depthinterviews, observation, and documentation involving MSME actors, particularly Dapur FNR and Lamodis, as a comparative study between businesses that apply storytelling and those that do not. The results show that storytelling marketing plays a significant role in streng the ning Brand awareness , Brand image, and consumer emotional engagement. MSMEs that consistently apply storytelling are able to build stronger Brand id entities through authentic narratives about production processes, businessvalues, andthe personal experiences of the owners. This contributes to increased trust, loyalty, and product attractiveness in the eyes of consumers. In contrast, MSMEs thatdo not utilize storytelling tendt of acelimitations in building emotional connections and Brand differentiation. Furthermore, theuse of digital media has proven to expand the reach of Brand storytelling mor eeffectively. The refore, storytelling marketing can serve as an effective marketing communication strategy for MSMEs to streng then local product Brand ing and enhance competitiveness in the digital era.